Assessing the Effects of Sports Disciplines on Body Composition and Bone Health: A Focus on Yoga, Weightlifting, and Long-Distance Running - Waza, Naseer Ud Din; Deol, Nishan Singh (Physical Education Theory and Methodology, 2025)
Background. Understanding how different sports influence bone health and body composition is key to improving athletic performance and overall well-being. Weightlifting, yoga, and long-distance running each have unique impacts on the body. This study offers insights into how specific sports disciplines shape bone health and body composition, providing valuable guidance for enhancing fitness and health recommendations. Objectives. The study aimed to assess the effects of weightlifting, yoga, and long-distance running on body composition and bone mineral density, highlighting how these activities significantly influence both factors. Materials and methods. A random sampling method was used to select ninety (N = 90) interuniversity athletes. The sample consisted of long-distance runners (n = 30), weightlifting athletes (n = 30), and yoga practitioners (n = 30). Bone mineral density was measured using the Achilles EXPII (Part 1) Bone Mineral Density Analyzer, while body composition was assessed with the GS6.5B Body Building Weight Test System (Version 1.0). Results. Significant differences were observed among the groups in bone mineral density F(2, 87) = 15.95, p = .000, body fat percentage F(2, 87) = 26.15, p = .000, and skeletal muscle mass F(2, 87) = 23.30, p = .000. A post-hoc LSD test showed that weightlifters had the highest bone mineral density and skeletal muscle mass, whereas long-distance runners demonstrated the lowest body fat percentage among the groups. Conclusions. The study revealed substantial differences in skeletal muscle mass, body fat percentage, and bone mineral density among weightlifters, yoga practitioners, and long-distance runners. These findings highlight the distinct physiological adaptations associated with each sport, emphasizing the need for customized training and health strategies to optimize performance and health outcomes across different athletic disciplines.